1989
DOI: 10.1007/bf00256935
|View full text |Cite
|
Sign up to set email alerts
|

Lung ventilation and perfusion scintigraphy in the follow up of repaired congenital diaphragmatic hernia

Abstract: To evaluate the effects of congenital diaphragmatic hernia (CDH) and pulmonary hypoplasia on subsequent lung function and development, we performed lung 133Xe ventilation and 99mTc perfusion scintigraphies in a group of infants who had undergone surgical repair of a severe left CDH with respiratory distress within the first 6 h of life. The initial lung scans performed in 15 children, 2-3 months of age, demonstrated a decreased ventilation in 7. In 9 children there was a trapping of 133Xe at the left lung base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 21 publications
4
25
0
1
Order By: Relevance
“…Nevertheless, our MRI-based flow measurements revealed reduction of the cross-sectional area and the flow parameters of the left pulmonary artery and shifting of the blood flow to the right side. These findings are in accordance with the scintigraphic findings reported earlier [6,17], indicating left-sided lung hypoplasia after left-sided diaphragmatic hernia and the reduction of the entire pulmonary vascular bed in hypoplastic lungs. Using velocity-encoded MRI, we found shortened acceleration times in the pulmonary arteries which is compatible with PAH [30,31].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, our MRI-based flow measurements revealed reduction of the cross-sectional area and the flow parameters of the left pulmonary artery and shifting of the blood flow to the right side. These findings are in accordance with the scintigraphic findings reported earlier [6,17], indicating left-sided lung hypoplasia after left-sided diaphragmatic hernia and the reduction of the entire pulmonary vascular bed in hypoplastic lungs. Using velocity-encoded MRI, we found shortened acceleration times in the pulmonary arteries which is compatible with PAH [30,31].…”
Section: Discussionsupporting
confidence: 94%
“…But the results of measurements of functional lung volumes by spirometry remain controversial [5,6]. Marven et al investigated 19 patients (mean age 11.5 years) in comparison with age-matched healthy controls and showed reduced total lung capacity and decreased maximum oxygen consumption [7].…”
Section: Introductionmentioning
confidence: 98%
“…A few reports, however, have documented the impact of pulmonary hypoplasia on mid-and longterm pulmonary function on pts' wellbeing [9,13,14,[20][21][22][23]. Previous follow-up studies have demonstrated functional pulmonary abnormalities in children who had survived the repair of a diaphragmatic defect [21]. Persistent reduction of blood flow in the lung on the affected side has also been observed [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 97%
“…Several perfusion studies in CDH survivors have demonstrated a reduced mean perfusion in the affected and contralateral lung compared to healthy neonates in the early postoperative period [1,4,6,7,[20][21][22] . In the subsequent follow-up, ventilation was shown to improve with age.…”
Section: Lung Perfusion Studymentioning
confidence: 99%